Industrial applications of repetitively pulsed lasers (analysis of precision problems). - Nasrullah, K.; Hall, T.A
Industrial applications of highly repetitive laser may cause precise exposure problems. This paper reports findings of an experimental study on integral gain accretion during repetitive excitation of distributed feedback dye lasers. To estimate the effect 10 to 20 pulses of second harmonic of a passively Q-Switched and mode-locked Nd:YAG laser were used to excite a distributed feedback dye laser (DFDL). The signals of DFDL and Nd:YAG laser were recorded by Imacon 675-streak camera with no relative delay. It was found that the peak of DFDL output envelope of pulses was delayed from peak of the excitation Nd:YAG envelope of pulses by more than one inter-pulse period (2L/C) of excitation laser. Various types of cases such as different excitation energies and inter-pulse time periods were studied and an intensity-based model was developed. Time delay between the peaks of pulse envelopes of Nd:YAG and DFDL was found to depend upon the inter-pulse period (2L/C) of the excitation laser. A computer program was used to simulate the experimentally measured delay to estimate thermal decay constants and energy retained by the medium. It was found that for smaller inter-pulse periods the effect of gradual gain build-up becomes very significant to affect some of the sensitive applications in welding and communication. This effect was used to measure thermal diffusion time constant of dye solutions.